Profitability, efficiency and risk in banking and microfinance - (:unkn) unknown (My University, 2022)
The main objective of our thesis is to analyse the explanatory factors of probability, efficiency and non-performing loans in the portfolio of financial institutions. The thesis consists of four chapters. The first chapter proposes to study the importance of customer segmentation on the risk level of the financial institution. To this end, we examine the relationship between the percentage of female borrowers and the risk level of microfinance institutions. We find a negative relationship between the percentage of female borrowers and the portfolio at risk, even though the share of women in the clientele of microfinance institutions tends to decrease. The second chapter analyses the impact of shareholder origin on the risk level of commercial banks. We examine the relationship between shareholder origin and risk in the Economic and Monetary Community of Central Africa. We find that locally owned banks operated with significantly higher non-performing loan ratios than their state-owned of foreign-owned counterparts. The third chapter analyses the determinants of inefficiency of microfinance institutions in the countries of the Central African Economic and Monetary Community and the West African Economic and Monetary Union. The results show that microfinance institutions less specialized in lending to women and younger microfinance institutions are more efficient and that competition worsens the efficiency of microfinance institutions in these countries. Finally, the fourth chapter examines the relationship between shareholder origin, market power and bank profitability. We find that locally owned banks and African owned banks are more profitable than other banks and that competition (market power) worsens (improves) their profitability.
Keywords: African Research